Answer:
Explanation:
Given the following explicit formula, we are to calculate the first four (4) terms of the sequence.
1) f(n) = 9+8n
When n = 1
f(1) = 9+8(1)
f(1) = 17
when n = 2
f(2) = 9+8(2)
= 9+16
= 25
When n = 3
f(3) = 9+8(3)
f(3) = 33
when n = 4
f(4) = 9+8(4)
= 41
= 25
The first four terms are 17, 25, 33 and 41
2) f(n) = 8(n+1)-13
When n = 1
f(1) = 8(2)-13
f(1) = 3
when n = 2
f(2) = 8(3)-13
= 24-13
= 11
When n = 3
f(3) = 8(4)-13
f(3) = 32-13
= 19
when n = 4
f(4) = 8(5)-13
= 40-13
= 27
The first four terms are 3, 11, 19 and 27
3) f(n) = 65-9n
When n = 1
f(1) = 65-9(1)
f(1) = 56
when n = 2
f(2) = 65-9(2)
= 65-18
= 47
When n = 3
f(3) = 65-9(3)
f(3) = 65-27
= 38
when n = 4
f(4) = 65-9(4)
= 65-36
= 29
The first four terms are 56, 47, 38 and 29